2015
DOI: 10.1249/mss.0000000000000649
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity, Sedentary Time, and Obesity in an International Sample of Children

Abstract: Greater MVPA and VPA were both associated with lower odds of obesity independent of sedentary behavior. Sedentary time was positively associated with obesity, but not independent of MVPA. Attaining at least 55 min·d of MVPA is associated with lower obesity in this multinational sample of children, which supports current guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
172
2
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 190 publications
(196 citation statements)
references
References 28 publications
(42 reference statements)
16
172
2
6
Order By: Relevance
“…Meeting/not meeting guidelines (≥60 min/d MVPA): VERY LOW q 2/3 studies reported favourable associations (Steele et al 2009;Martinez-Gomez et al 2010b); 1/3 studies reported null associations (Mendoza et al 2012) Total PA: 9/22 studies reported favourable associations (Duncan et al 2008;Riddoch et al 2009;Steele et al 2009;Belcher et al 2010;Ferrar and Olds 2010;Owen et al 2010;Mark and Janssen 2011;Ekstedt et al 2013;Manios et al 2013) 8/22 studies reported mixed favourable and null associations (Andersen et al 2006;Duncan et al 2006;Ness et al 2007;Ortega et al 2007;Dollman et al 2010;Ruiz et al 2011;Tudor-Locke et al 2011;Jimenez-Pavon et al 2013c) 3/22 studies reported null associations Hands et al 2009;Martinez-Gomez et al 2012 (Ekelund et al 2004;Lohman et al 2006;Steele et al 2009;Martinez-Gomez et al 2010b;Mark and Janssen 2011;Sayers et al 2011;Chung et al 2012;Martinez-Gomez et al 2012;Jimenez-Pavon et al 2013a;Katzmarzyk et al 2015b). 4/15 studies reported mixed favourable and null associations Belcher et al 2010;Kelly et al 2010;Jimenez-Pavon et al 2013c) 1/15 studies reported mixed null and unfavourable associations ) MVPA: 20/30 studies reported favourable associations (Ekelund et al 2004;…”
Section: No Serious Imprecisionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meeting/not meeting guidelines (≥60 min/d MVPA): VERY LOW q 2/3 studies reported favourable associations (Steele et al 2009;Martinez-Gomez et al 2010b); 1/3 studies reported null associations (Mendoza et al 2012) Total PA: 9/22 studies reported favourable associations (Duncan et al 2008;Riddoch et al 2009;Steele et al 2009;Belcher et al 2010;Ferrar and Olds 2010;Owen et al 2010;Mark and Janssen 2011;Ekstedt et al 2013;Manios et al 2013) 8/22 studies reported mixed favourable and null associations (Andersen et al 2006;Duncan et al 2006;Ness et al 2007;Ortega et al 2007;Dollman et al 2010;Ruiz et al 2011;Tudor-Locke et al 2011;Jimenez-Pavon et al 2013c) 3/22 studies reported null associations Hands et al 2009;Martinez-Gomez et al 2012 (Ekelund et al 2004;Lohman et al 2006;Steele et al 2009;Martinez-Gomez et al 2010b;Mark and Janssen 2011;Sayers et al 2011;Chung et al 2012;Martinez-Gomez et al 2012;Jimenez-Pavon et al 2013a;Katzmarzyk et al 2015b). 4/15 studies reported mixed favourable and null associations Belcher et al 2010;Kelly et al 2010;Jimenez-Pavon et al 2013c) 1/15 studies reported mixed null and unfavourable associations ) MVPA: 20/30 studies reported favourable associations (Ekelund et al 2004;…”
Section: No Serious Imprecisionmentioning
confidence: 99%
“…4/15 studies reported mixed favourable and null associations Belcher et al 2010;Kelly et al 2010;Jimenez-Pavon et al 2013c) 1/15 studies reported mixed null and unfavourable associations ) MVPA: 20/30 studies reported favourable associations (Ekelund et al 2004;Lohman et al 2006;Ness et al 2007;Stevens et al 2007;Mark and Janssen 2009;Riddoch et al 2009;Steele et al 2009;Belcher et al 2010;Martinez-Gomez et al 2010b;Holman et al 2011;Grydeland et al 2012;Lawman et al 2012;Carson et al 2013;Ekstedt et al 2013;Jimenez-Pavon et al 2013a;Taverno Ross et al 2013;da Silva et al 2014;Young et al 2014;Katzmarzyk et al 2015aKatzmarzyk et al , 2015b) 6/30 studies reported mixed favourable and null associations Peart et al 2011;Ruiz et al 2011;Mendoza et al 2012;St George et al 2013;Jimenez-Pavon et al 2013c) 3/30 studies reported null associations (Hurtig-Wennlof et al 2007;Ortega et al 2007;Martinez-Gomez et al 2012) 1/30 studies reported mixed null and unfavourable associations (Mark and Janssen 2009;Holman et al 2011) 3 studies examined bouts of MVPA and associations were favourable (2/3 studies; Holman et al 2011;da Silva et al 2014) or mixed (favourable and null; 1/3 studies; Mark and Janssen 2009) MPA: 2/10 studies reported favourable associations …”
Section: No Serious Imprecisionmentioning
confidence: 99%
“…30 After exclusion of total sleep time and awake non-wear time (any sequence of ⩾ 20 consecutive minutes of 0 activity counts), MVPA was defined as all activity ⩾ 574 counts per 15 s and total SED as all movement ⩽ 25 counts per 15 s, consistent with the widely used Evenson cutoffs. 29,31,32 Statistical analyses. Multilevel linear regression models were used to examine the association between birth weight and BMI-for-age z-scores.…”
Section: Measurementsmentioning
confidence: 99%
“…In relation to this the most relevant risk factors that contribute to the excessive body weight gain in adolescents are primarily a sedentary life style or lack of physical activity, like exercise (Díaz et al, 2015, Ten et al, 2016, primarily influenced by the excessive number of hours spent in front of a TV (Katzmarzyk et al, 2015, Laurson et al, 2015 or electronic entertainment devices, together with hypercaloric eating habits where the family has a significant influence (He et al, 2015, Flattum et al, 2015. The previous overview, all this is known as an obesogenic environment (Miqueleiz et al, 2015), which together with biological factors like certain hormones that stimulate hunger and satiety, the baby's weight at birth and genetic load, condition the excess of body fat in adolescents and metabolic problems (González et al, 2015., Landgraf et al, 2015.…”
Section: Introductionmentioning
confidence: 99%